2020
DOI: 10.1002/advs.202002797
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species‐Regulating Strategies Based on Nanomaterials for Disease Treatment

Abstract: Reactive oxygen species (ROS) play an essential role in physiological and pathological processes. Studies on the regulation of ROS for disease treatments have caused wide concern, mainly involving the topics in ROS‐regulating therapy such as antioxidant therapy triggered by ROS scavengers and ROS‐induced toxic therapy mediated by ROS‐elevation agents. Benefiting from the remarkable advances of nanotechnology, a large number of nanomaterials with the ROS‐regulating ability are developed to seek new and effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
144
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(146 citation statements)
references
References 310 publications
(368 reference statements)
1
144
0
1
Order By: Relevance
“…MXene exerts its biological activity on living cells by the generation of reactive oxygen species (ROS). This property makes MXenes exhibit anticancer potential due to the already increased baseline amount of reactive oxygen species within cancer cells, owing to increased anabolic and catabolic reactions [27]. ROS plays a key role in cell metabolism and survival, as well as in the cytotoxicity mechanisms of various classes of carbon-based nanomaterials [12].…”
Section: Discussionmentioning
confidence: 99%
“…MXene exerts its biological activity on living cells by the generation of reactive oxygen species (ROS). This property makes MXenes exhibit anticancer potential due to the already increased baseline amount of reactive oxygen species within cancer cells, owing to increased anabolic and catabolic reactions [27]. ROS plays a key role in cell metabolism and survival, as well as in the cytotoxicity mechanisms of various classes of carbon-based nanomaterials [12].…”
Section: Discussionmentioning
confidence: 99%
“…Fullerene (C 60 ) is a form of crystalline carbon with radical scavenging abilities attributed to its conjugated double bonds with good electron affinity, which makes it an excellent electron acceptor. The C 60 can capture ROS by accepting their unpaired electron [ [74] , [75] , [76] ]. Studies have shown that both superoxide and hydroxyl radicals were immobilized on the fullerene surface [ 77 ] ( Fig.…”
Section: Ros-scavenging Nanomaterials That Promote Oxidative Damage Repair and Mechanisms Governing This Repairmentioning
confidence: 99%
“…The optimal ratio in the reduction process was adopted from the previous reports. 9,50 Initially, a stock solution of GO (1 mL, C = 1 mg mL −1 ) was diluted with DI water (9 mL), and the lutein solution (20 µL of 2-mM in DI water) was thoroughly mixed. The pH was maintained within 9-10 by adding NaOH (1 mL of 1-M), and then the prepared solution was stirred at 95°C at 500 rpm.…”
Section: Synthesis Of the Lu-rgo Complexmentioning
confidence: 99%
“…8 Additionally, carotenoids have been reported to decrease several reactive oxygen species (ROS). 9 Therefore, carotenoids present in lutein could be involved in antioxidant activities occurring in the human body.…”
Section: Introductionmentioning
confidence: 99%